In vitro transdermal absorption of Al2O3 nanoparticles. (September 2019) - Mauro, Marcella; Crosera, Matteo; Bovenzi, Massimo; Adami, Gianpiero; Maina, Giovanni; Baracchini, Elena; Larese Filon, Francesca
Abstract: Dermal exposure to Aluminium nanoparticles (AlNPs) can occur in occupationally- and non occupationally exposed- population, due to the use of Al salts-based antiperspirants. No AlNPs transdermal permeation data exists. Our study investigated in vitro the permeation of 30–60 nm Al2 O3 NPs dispersed in synthetic sweat (20 g/L) using excised human skin on Franz cells. Experiments were performed using intact (experiment 1) and needle-abraded skin (experiment 2). After 24 h traces of Al were detectable in receiving solution of exposed cells (35.0 ± 6.0 ng/cm 2 for intact and 88.5 ± 34.2 ng/cm 2 for damaged skin, mean and SD) and in blank cells (36.3 ± 7.0 ng/cm 2 ), without statistical significance ( p  = 0.08, Mann-Whitney test). The average amount of Al into intact and damaged skin samples was 3.96 ± 0.20 μg/cm 2 for intact and 4.36 ± 0.47 μg/cm 2 for damaged skin ( p  = 0.08). Al content was similar in epidermal and dermal layers of intact and damaged skin (1.95 ± 0.13 μg/cm 2 and 2.31 ± 0.12 μg/cm 2 epidermal, 2.01 ± 0.25 μg/cm 2 and 2.05 ± 0.35 μg/cm 2 dermal). Al is a trace element in human body and the amount found in receiving solutions could be due as background impurity. This data suggest a reassuring transdermal permeation profile for Al2 O3 NPs. Graphical abstract: Unlabelled Image Highlights: No data on skin permeation of Aluminium oxides NPs are available. In vitro permeation of Al2 O3 NPs (53 ± 15 nm) has been assessed using Franz cells. Intact and damaged human full thickness skin samples have been used. Only traces of Al were detected in receiving solution in all types of exposed cells.